Origin of human library concept in Vedic knowledge system: some evidences - Balakailasanathasarma, M.; Navaneethakrishnan, S. (Royal Asiatic Society of Sri Lanka, 2018)
All cultures have found ingenious ways to pass on their knowledge systems, through developing formal and informal ways of communication and preservation. When we examine some signiﬁcant ways in which India preserved and transmitted its knowledge, we see that lndia’s oral tradition has followed both ﬁxed and ﬂoating patterns of transmission, in codiﬁed and un-codiﬁed forms. While the knowledge contained in the Vedas and its ancillary branches came to be transmitted through an established, meticulous code of memorization. Human library is a concept where the human beings are treated as books for reference purpose. This research study identified the origin of the human library concept in Vedic knowledge system. This interdisciplinary study specially focused on this area in a different point of view to develop the new idea for debate. Using mixed method with exploratory research method and descriptive research method, this study explains the identified elements of the Vedic knowledge system as like as human library concept. Objective of this study is to identify some evidences to prove the origin of the human library concept in Vedic knowledge system. Findings of this study identified Veda ṛịshes as first human libraries, who received the spiritual knowledge from god, preserved it in their memory, and disseminate it to the society. While the codiﬁed system of handing down Vedic corpus became dependent on an organized system of learning through the Guru-Sịshya tradition, the narrative-performative tradition of recitation carried on the dissemination of Vedic knowledge system.
Keywords: Human library; Vedic literature; Sanskrit Literature